Academic Burnout Mahasiswa IAIN Langsa Ditinjau dari Demografi dan Strategi Coping - Nengsih, Nengsih; Icanda, Nadica (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2024)
Academic burnout is often associated with various academic issues that impact students' learning performance. One way to address this academic pressure is through coping strategies, which are individual efforts to manage or deal with problems and stress. This study measures coping strategies through three types: problem-focused coping, emotion-focused coping, and maladaptive coping. The study aims to analyze the differences in academic burnout levels among IAIN Langsa students based on demographics and coping strategies employed. The research method used is descriptive inferential quantitative, with incidental sampling techniques applied to 372 student participants. Data analysis was conducted using two-way ANOVA. The results indicate significant differences in students' academic burnout levels based on demographics and coping strategies, with a significance value of 0.000 (p < 0.05). These findings suggest that the coping strategies used by students, particularly maladaptive coping, have a substantial influence on the level of academic burnout experienced. Therefore, it is essential to encourage the use of more adaptive coping strategies to mitigate the effects of burnout among students.